Oral communication in context - Sayuno, Cheeno Marlo (Makati City : Diwa Learning Systems, Inc., 2019)
"Communication is part of our basic functions as social being. We all have the innate ability to communicate. While there are good oral speakers by nature, others have plenty of room to improve and to unleash their potentials. Oral communication in Context (Second Edition) module provides you with a wide array of means to practice your oral communication skills. Its tailor-made activities will holistically shape you into an excellent and effective communicator in various contexts and situations. It will introduce you to elements, theories, and processes of communication and equip you with various communication strategies that you can apply to different types of speeches explored through researches explored through research-, project-, and performance-based activities. Furthermore, it will prepare you in facing the communication challenges of the fast changing world through the use of five types of instruction- discovery, integration, inquiry, and collaboration- coupled with 21st century learning skills. "
Includes bibliography.
English text.
Keywords: Oral communication; Public speaking; Speech